Development of innovative audiobooks to optimize e-learning - Fitriati, Azmi; Hartikasari, Annisa Ilma; Pandansari, Tiara; Pramurinda, Rezky; Nuryana, Ilham; Ong, Eng Tek (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
E-learning requires innovative teaching materials to improve the quality of learning. But currently, e-learning cannot increase motivation and learning outcomes. Materials and media should adapt to the learning needs of e-learning. This study aimed to develop and test the effectiveness of innovative audiobooks for practical computers. The research method used is research and development. The stages of this model are analysis, design, development, implementation, and evaluation. Instruments used are interviews, observation, validation, questionnaires, and tests. Then, descriptive statistical analysis was used. The research subjects are lecturers and students. The number of respondents was as many as 115 people. The results of the analysis showed that the use of audiobooks could improve students' understanding and skills. Audiobook is an alternative e-learning media. Audiobooks have been designed in a flexible and user-friendly. Audiobooks are equipped with learning sounds and videos that users need. So that users can understand and practice it independently. Users can easily learn and operate it. Based on the evaluation results, it is known that the user has perceived usefulness and ease of use. Users feel satisfied and have a positive attitude. This attitude will foster interest in and actual use of audiobooks. Furthermore, innovative digital books can be developed for other subjects. Students can use flexible audiobooks be outonomous to improve their understanding and skills.